Characterisation of the molecular properties of scleroglucan as an alternative rigid rod molecule to xanthan gum for oropharyngeal dysphagia. (April 2020) - Li, Xinxin; Lu, Yudong; Adams, Gary G.; Zobel, Hanne; Ballance, Simon; Wolf, Bettina; Harding, Stephen E.
Abstract: Scleroglucan, a neutral β(1–3) glucan with β(1–6) glucan branches every third residue, is being considered as an alternative rod-like, shear thinning high molecular weight β-glucan based polysaccharide to xanthan gum for the management of patients with oropharyngeal dysphagia. It is therefore important to understand more fully its hydrodynamic properties in solution, in particular heterogeneity, molecular weight distribution and its behaviour in the presence of mucin glycoproteins. A commercially purified scleroglucan preparation produced by fermentation of the filamentous fungus Sclerotium rolfsii was analysed in deionised distilled water with 0.02% added azide. Sedimentation velocity in the analytical ultracentrifuge showed the scleroglucan preparation to be unimodal at concentrations >0.75 mg/ml which resolved into two components at lower concentration and with partial reversibility between the components. Sedimentation coefficient versus concentration plots showed significant hydrodynamic non-ideality. Self-association behaviour was confirmed by sedimentation equilibrium experiments with molecular weights between ~3 × 10 6  g/mol to ~5 × 10 6  g/mol after correcting for thermodynamic non-ideality. SEC-MALS-viscosity experiments showed a transition between a rod-shape at lower molar masses to a more flexible structure at higher masses consistent with previous observations. Sedimentation velocity experiments also showed no evidence for potentially problematic interactions with submaxillary mucin. Graphical abstract: Image 1 Highlights: Scleroglucan considered as alternative to xanthan. Sedimentation velocity shows partial reversible self-association. Associative behaviour confirmed by sedimentation equilibrium. SEC-MALS and viscosity show transition between a rod to more flexible structure. No problematic interactions with submaxillary mucin.